Optimal Fiscal Feedback on Debt in an Economy with Nominal Rigidities. - Kirsanova, T; Wren-Lewis, S (2006)
We examine the impact of different degrees of fiscal feedback on debt in an economy with nominal rigidities where monetary policy is optimal. We look at the extent to which different degrees of fiscal feedback enhances or detracts from the ability of the monetary authorities to stabilise output and inflation. Using an objective function derived from utility, we find the optimal level of fiscal feedback to be small. There is a clear discontinuity in the behaviour of monetary policy and welfare either side of this optimal level. As the extent of fiscal feedback increases, optimal monetary policy becomes less active because fiscal feedback tends to deflate inflationary shocks. However this fiscal stabilisation is less efficient than monetary policy, and so welfare declines. In contrast, if fiscal feedback falls below some critical value, either the model becomes indeterminate, or optimal monetary policy becomes strongly passive, and this passive monetary policy leads to a sharp deterioration in welfare.